Empowerment of Cadres in the Sensation Program (Healthy Anti-Hypertension Gymnastics) Efforts to Handle Hypertension - Margatot, Didik Iman (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Hypertension generally occurs at the age of 45-64 years. The age of 45-64 years is an age grouping that is included in the elderly (elderly), so that in terms of age grouping, hypertension often occurs in the elderly (elderly). The role of elderly cadres is very important in improving the quality of life of an elderly person. Empowering elderly cadres in providing motivation for the elderly to deal with hypertension by doing healthy anti-hypertension gymnastics (SENSASI) is very effective in preventing complications of hypertension itself, so that elderly people who experience hypertension can control their blood pressure. The method of implementing this community service activity is by providing counseling and teaching hypertension gymnastics to cadres and the elderly. The results of community service activities obtained that the increase in knowledge of a cadre after being given education, namely 15 cadres (100%) there were cadres who had a good level of knowledge and 3 cadres were able to revive hypertension gymnastics movements properly and correctly.